2013
DOI: 10.1111/bph.12109
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological potential of biogenic amine–polyamine interactions beyond neurotransmission

Abstract: Histamine, serotonin and dopamine are biogenic amines involved in intercellular communication with multiple effects on human pathophysiology. They are products of two highly homologous enzymes, histidine decarboxylase and L-aromatic amino acid decarboxylase, and transmit their signals through different receptors and signal transduction mechanisms. Polyamines derived from ornithine (putrescine, spermidine and spermine) are mainly involved in intracellular effects related to cell proliferation and death mechanis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(35 citation statements)
references
References 134 publications
0
34
0
1
Order By: Relevance
“…In fact, the polyamine backbones, mainly spermine, spermidine, and putrescine, are ubiquitous cellular components playing particularly important roles in defence of injury for the central nervous system (Adibhatla, Hatcher, Sailor, & Dempsey, 2002;Sánchez-Jiménez, Ruiz-Pérez, Urdiales, & Medina, 2012). Previous studies have indicated that exogenous polyamines and their derivatives are effective in curing neurotrauma, like mechanical injuries, neurotoxins, and cerebrovascular mal- Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, the polyamine backbones, mainly spermine, spermidine, and putrescine, are ubiquitous cellular components playing particularly important roles in defence of injury for the central nervous system (Adibhatla, Hatcher, Sailor, & Dempsey, 2002;Sánchez-Jiménez, Ruiz-Pérez, Urdiales, & Medina, 2012). Previous studies have indicated that exogenous polyamines and their derivatives are effective in curing neurotrauma, like mechanical injuries, neurotoxins, and cerebrovascular mal- Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Sin embargo, aún quedan muchas lagunas de información sobre las cadenas de acontecimientos moleculares implicados en cada caso. Descifrar del modo más completo posible la red de interacciones que se establecen en cada tipo celular, y entre ellos, es fundamental para poder intervenir en la larga lista de patologías en las que las aminas están implicadas (8,9). Desde hace más de una década reclamamos la necesidad de hacer un esfuerzo de investigación colaborativa y multidisciplinar que incluya el apoyo de recursos biocomputacionales de valor predictivo y la posterior validación experimental de las predicciones (1,3,4,8-11).…”
Section: Es/es/divulgacion-ciencia-para-todos_10/acercate-a-nuestroscunclassified
“…Intra-and intercellular crosstalk among histamine and amine-related components has important pathophysiological consequences, as reviewed in detail by Sánchez-Jiménez et al (2013). Histamine and the immune system have a long history, with the H1 and H2 receptors much studied as key players.…”
Section: Ehrs European Histamine Research Society; Esf Cost Europeamentioning
confidence: 99%